Tolerance of Barbonymus schwanenfeldii under sulfide exposure - Azimah, Apendi; Ling, Teck Yee; Lee, Nyanti; Sim, Siong Fong; Jongkar, Grinang; Karen Suan, Ping Lee; Tonny, Ganyai (Bioflux Publisher, 2018)
Hydrogen sulfide, a common occurrence in hydroelectric dam environment, is potentially toxic to living organisms in the environment. However, studies on the response of indigenous fish species when exposed to sulfide are still lacking in literature. Thus, behavioral responses and mortality of an indigenous fish species, Barbonymus schwanenfeldii, were determined in the laboratory where juveniles were exposed to different concentrations of sulfide. Three experiments were conducted during the exposure, namely, gradual sulfide exposure, sulfide exposure under lowering DO condition and gradual sulfide exposure under lowering pH condition. Methylene blue method was used to analyze the water for actual total sulfide concentrations. Behavioral responses, dissolved oxygen level and pH were taken and recorded. Four behavioral responses observed in sulfidic water were huddling, aquatic surface respiration, loss of equilibrium and mortality. However, in negative control no such responses were observed during the duration of the experiment. As the sulfide concentration increased, the time taken to the occurrence of behavioral responses decreased indicating increased toxicity. The LC50 at 6 h was estimated as 507.8 µg L -1 total sulfide (490 µg L -1 H2S) at 95% confidence level. Under sulfide exposure in lowering pH condition, mortality was significantly faster than the other two experimental conditions. This study shows that juveniles showed behavioral response to all sulfide concentrations tested and lowering both DO and pH levels increased the sulfidic toxicity as they led to faster mortality of juveniles. Key Words: huddling, aquatic surface respiration, loss of equilibrium, toxicity, mortality.